The Effect of Subtitled Videos Combined with the Flipped Classroom Method on Students’ Reading Comprehension - Yani, Ni Kadek Refi Marsita; Kusuma, I Putu Indra; Budiarta, Luh Gd Rahayu (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study aims to explore the effect of integrating subtitled videos with the flipped classroom method on students' reading comprehension. This is because many Indonesian students still face challenges due to limited vocabulary, poor grammar mastery, and low motivation, even though reading comprehension plays a crucial role in English language acquisition. A quasi-experimental design was used in this study, involving two groups of eleventh-grade students at SMA Negeri 1 Seririt. The two groups were an experimental group treated with subtitled videos using the flipped classroom method and a control group receiving traditional printed text instruction. The findings of this study showed a statistically significant difference in post-test scores between the two groups, with the experimental group being higher than the control group. Thus, the implementation of subtitled videos allows students to access the content repeatedly and engage visually and textually. Meanwhile, the flipped classroom approach increases students' active participation and self-directed learning. These results indicate that combining subtitled videos with flipped classroom instruction effectively improves reading comprehension. Also, these results demonstrate the potential of student-centered, multimedia-enhanced strategies to enrich language learning and offer practical implications for future instructional design.